Blockchain adoption at German logistics service providers - Oliver Kühn; Axel Jacob; Michael Schüller (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: The study provides a recent overview of the diffusion of blockchain technology in the logistics industry. It reveals the adoption of blockchain technology at German logistics service providers (LSPs) and their expectations regarding the future relevance of the technology. Based on the TOE Framework adoption supporting and inhibiting factors are identified. Methodology: In a first step, LSPs listed in the 'Die Top 100 der Logistik 2016/2017' were contacted and questioned about their blockchain activities. Based on the responses, qualitative interviews were conducted with seven participants as part of a three-stage Delphi study. Findings: In particular small and medium-sized German LSPs are currently hardly involved in blockchain technology. Larger LSPs are beginning to define their own use cases and are trying to develop them further in joint projects with partners. A systematic use is currently not taking place. Originality: The study reveals the current discrepancy between rapidly evolving theoretical approaches for the use of blockchain technology in logistics, on the one hand, and the absence of the technology in everyday operations on the other hand. It also reveals a reluctant attitude of the management towards the technology.
urn:nbn:de:gbv:830-882.054336; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 650; Blockchain adoption; German logistics service providers; TOE framework; Delphi method